The relationship between behavior, history of contact with patients and home environment with the incidence of tuberculosis in the working area of the Wakobhalu Muna Public Health Center - Waode Mitha Fatrisya S; Yasnani Yasnani; Siti Selfia (PT WIM Solusi Prima, 2026)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis. Tuberculosis can attack the lungs and can attack all parts of the body. Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium Tuberculosis. Globally, approximately 1.25 million people will die from TB in 2023. The purpose of this study is to determine the factors related to the causes of tuberculosis in the working area of ​​the Wakobhalu Community Health Center in 2026. The cross-sectional research methodology was used in the form of a quantitative study. Data were analyzed using the chi-square test. The population in this study were patients visiting the Wakobhalu Community Health Center. And the sample in this study were 32 TB-positive patients and 32 TB-negative patients. The sampling technique used was purposive sampling, namely the selection of samples based on certain criteria. The research instruments used were a consent informant sheet, a questionnaire sheet, stationery, documentation tools, and a computer. The results of the study showed that the knowledge variable had a significant value of 0.001, the home environment variable had a significant value of 0.006, and the history of contact with sufferers variable had a significant value of 0.000. The conclusion is that there is a relationship between knowledge, home environment, and history of contact with sufferers with the cause of Tuberculosis. Kata Kunci: Lingkungan Rumah, Perilaku,Riwayat Kontak dengan Penderita,Tuberkulosis